Analysis of Factors Related to Pregnancy Indications, Parity, and Psychology of Normal Labor Pain to the Incidence of Sectio Caesarean (SC) Labor at Jakarta Port Hospital - Fitria Anggraini (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Childbirth is a natural process in which a mother gives birth to her baby. In some cases, normal delivery can turn into Sectio Caesarea (SC) delivery, namely via caesarean section, which involves an incision in the abdominal wall and uterus. The high rate of SC births is a concern in many countries, including Indonesia, because it can have significant health and economic impacts on mothers and babies. To determine the factors indicating pregnancy, parity and the psychology of normal labor pain on the incidence of section cesarean delivery (SC) at the Jakarta Harbor Hospital in 2024. The sample size in this study used all maternal patients who visited the Jakarta Harbor Hospital based on secondary data on mothers giving birth at the Jakarta Harbor Hospital recorded from January to December 2023 totaling 180 people. The sampling technique is non-probability sampling with a purposive method. The data used is primary data obtained from the results of a questionnaire asking about indications of pregnancy, parity and the psychology of normal labor pain. The data analysis used was univariate and bivariate analysis using the chi square test. There is a relationship between indications of pregnancy, parity and the psychology of normal labor pain on the incidence of Sectio Caesarea (SC) delivery at Jakarta Harbor Hospital with a P-value < 0.005. It is hoped that all health workers will pay attention to the health of women giving birth and attempts at SC delivery to prevent risks occurring during delivery.